(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the frequency of left main coronary artery disease in patients presenting with acute coronary syndrome having ST elevation in lead avR. Study Design: Descriptive/ cross sectional study Place and Duration of Study: This study was conducted at the Department of Cardiology, Liaquat National hospital, Karachi from March 2019 to September 2019. Materials and Methods: Total 246 patients presented with acute coronary syndrome had ST elevation in lead avR > 0.5 mm on ECG were included. Demographic data were recorded. All patients underwent coronary angiography to diagnose coronary artery disease. SPSS version-21 was used. Descriptive statistics were calculated. Stratification was done and chi square test was applied. P-value ≤0.05 was taken as significance. Results: There were 174 male and 72 female patients. The mean duration of chest pain was 45.01±14.40 minutes. 42.3% were diabetic, 58.9% were hypertensive, 37.8% were smokers, and 42.3% were obese. The left main stem disease was observed in 201(81.7%) patients and its significant association was observed with smoking and obesity with p<0.05. Conclusion: The ST-segment elevation on lead aVR was an important predictor of occurrence of left main disease in patients with ACS.